Experimental Pesah or, How do you Eat a Lamb while Holding a Staff in your Hand?. Issue 1 (2nd January 2019) - Prosic, Tamara
ABSTRACT: The Passover festival has been the ritual expression of Jewish cultural identity ever since the Old Testament got the form it has today. This article looks at the ways cultural identity was expressed in antiquity, critiques the traditional prioritising of the story of exodus over its biblical ritual expression in understanding ancient Jewish identity and explores various Pesah sacrifice instructions in Exodus 12 as an implicit polemical ritual discourse engaged in constructing a ritual of cultural distinction. The article pays close attention to the tension between the invented and the real of the instructions, and attempts to identify the possible cultural other against whom some of the Exodus instructions were constructed.